Tingkat Pengetahuan, Kepatuhan Konsumsi Tablet Tambah Darah dan Asupan Zat Besi (Fe) dengan Status Anemia pada Remaja Putri di SMKN 1 Molawe Kecamatan Molawe Kabupaten Konawe Utara - Rianti, Rianti; Fatmawati, Fatmawati; Suwarni, Suwarni (Jurnal Gizi Ilmiah, 2022)
Background : Anemia in adolescent girls is a condition in which the blood hemoglobin level of adolescents is below normal (12 mg/dl). Anemia causes low birth weight babies, growth and development is not optimal and reduces learning achievement. Data from the Molawe Health Center showed that 60 young women who received blood-added tablets received 100% and only 6 people took blood-added tablets. The purpose of this study was to determine the relationship between the level of knowledge, compliance with blood supplement consumption and intake of iron (Fe) on anemia status in adolescent girls. Methods: This type of research is quantitative with a cross sectional study design. The population is all female adolescent students in grades X and XI at SMKN 1 Molawe, Molawe District, North Konawe Regency as many as 54 people and the sample of this research is all female adolescent students in grades X and XI as many as 35 people. Sampling used proportional stratified random sampling. Data on knowledge and compliance with Fe tablet consumption were obtained by questionnaire, data on iron intake was obtained by means of 2x24 hour recall. Anemia data was obtained by measuring hemoglobin using an easy touch meter. Data were analyzed using the Fisher Exact test for the compliance variable, while knowledge and iron intake used the Pearson correlation test. Results: The level of knowledge of the sample, most of them were sufficient, namely 88.6%, adherence to the consumption of blood-added tablets was mostly obedient, namely 62.9%, iron intake was mostly sufficient, namely 71.4% and anemia status was mostly not anemic, namely 74, 3%. The results of the Pearson correlation test on the relationship between knowledge and anemia status obtained p=0,029 and r = 0.184, and the relationship between iron intake and anemia status obtained p=0,019 and r = 0.395 while the fisher exact test results obtained a p=0.000 for adherence to the consumption of added tablets. blood and anemia status. Conclusion: There is a very weak positive relationship between knowledge and anemia status, there is a relationship between adherence to blood supplement consumption and anemia status and there is a weak positive relationship between iron (Fe) intake and anemia status in adolescent girls at SMKN 1 Molawe, Molawe District, Molawe Regency. North Konawe. This study suggests for young women at SMKN 1 Molawe to increase adherence to consuming blood-added tablets and limit consumption of tea and coffee, for Molawe Health Center to be used as a basis for increasing the scope of distribution of blood-added tablets to adolescent girls and for further researchers to examine other variables such as family support and the habit of consuming foods that inhibit iron absorption